The MLB encyclopedia - Flynn, Brendan, 1977- (Minneapolis, Minnesota : Abdo reference, 2022)
Alongside both historic and more recent photographs, readers will learn about each MLB team's history, greatest seasons, greatest players, and team records. In addition, the book offers an in-depth introduction about the sport's history, a section on star players, and information on the statistical leaders in various categories.
The history of Major League Baseball -- MLB teams -- Star players -- Honorable mentions -- MLB-all-time leaders.
School Library Journal, April 2022
Includes bibliographical references (page 189) and index.
6.4
5-8
1050L
Keywords: Baseball -- United States -- Encyclopedias, Juvenile; Baseball players -- United States -- Encyclopedias, Juvenile; Baseball -- Encyclopedias; Baseball players -- Encyclopedias; Encyclopedias; Baseball; Baseball players; Sports records